1999
DOI: 10.1037/0096-1523.25.3.661
|View full text |Cite
|
Sign up to set email alerts
|

On the distinction between visual salience and stimulus-driven attentional capture.

Abstract: It is often assumed that the efficient detection of salient visual objects in search reflects stimulus-driven attentional capture. Evidence for this assumption, however, comes from tasks in which the salient object is task relevant and therefore may elicit a deliberate deployment of attention. In 9 experiments, participants searched for a nonsalient target (vertical among tilted bars). In each display, 1 bar was highly salient in a different dimension (e.g., color or motion). When the target and salient elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
432
13
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(483 citation statements)
references
References 48 publications
(120 reference statements)
34
432
13
4
Order By: Relevance
“…When cueing effects are found when the location cue has no predictive value, this result is typically considered to be evidence that cueing is exogenous (bottom-up) and automatic (Jonides, 1981;LaBerge, 1981;Yantis & Jonides, 1990). Indeed, similar arguments were raised by Yantis and Egeth (1999) in the context of attentional capture. Yantis and Egeth argued that in order to determine whether particular effects are bottom-up, "It is necessary to observe the attentional effects of the attribute in question under conditions in which that attribute is explicitly task irrelevant, so that there is no incentive for the observer to attend to it deliberately" (p. 662-663).…”
Section: Methodsmentioning
confidence: 77%
“…When cueing effects are found when the location cue has no predictive value, this result is typically considered to be evidence that cueing is exogenous (bottom-up) and automatic (Jonides, 1981;LaBerge, 1981;Yantis & Jonides, 1990). Indeed, similar arguments were raised by Yantis and Egeth (1999) in the context of attentional capture. Yantis and Egeth argued that in order to determine whether particular effects are bottom-up, "It is necessary to observe the attentional effects of the attribute in question under conditions in which that attribute is explicitly task irrelevant, so that there is no incentive for the observer to attend to it deliberately" (p. 662-663).…”
Section: Methodsmentioning
confidence: 77%
“…For example, finding a green digit among red ones reduces the time taken to detect the target because the unique color of the target causes it to be more salient and to pop-out from the background of red distracters. This pattern has been found in particular if the object is relevant for the task (Yantis and Egeth 1999), but even persists if attending to the object that pops-out is known to be irrelevant and disadvantageous to the performance of the task (e.g., Pashler 1988;Theeuwes 1991Theeuwes , 1992. Especially, unique colors (e.g., Nagy and Winterbottom 2000;Galfano 2000, 2001;Turatto et al 2004) and luminance contrasts (Enns et al 2001) seem very effective at capturing attention.…”
Section: Theoretical Accounts Of the Effect Of Cueing On Perceptual Amentioning
confidence: 96%
“…An argument put forward to favour this proposal is the observation that irrelevant distracters with a unique feature capture attention (Jonides and Yantis, 1988) or gaze (Theeuwes et al, 1999;van Zoest et al, 2004) and elicit electrophysiological responses preceding activity related to processing of the relevant target (Hickey et al, 2006). In contrast, other studies using similar paradigms found that stimulus relevance is a crucial determinant of attentional capture and may affect early cortical processing of visual stimuli (Eimer and Kiss, 2008;Leblanc et al, 2008;Ptak et al, 2011;Yantis and Egeth, 1999). For instance, the capture of attention by goal-relevant features modulates event-related potentials (ERPs) approximately 180 ms after stimulus onset (Leblanc et al, 2008).…”
Section: Introductionmentioning
confidence: 96%